Hypogonadism in leprosy males - de Oliveira Andrade, Luis Jesuino; Oliveira, Moema Farias; França, Larissa Santos; França de Sousa, Ana Libia Oliveira; Andrade, Cristina Setenta; de Jesus, Humberto Barreto (Revista de Ciências Médicas e Biológicas, 2012)
Context and objective: Leprosy is a chronic systemic infectious disease caused by Mycobacterium leprae (Hansen’s bacillus). It is a problem of public health concern mainly because of its social stigma and discrimination. Hypogonadism in male with Leprosy can occur due the involvement testicular of lepromatous disease. The aim this study here was to evaluate the gonadal function in male with chronic leprosy. Study design: Cross-sectional study in a leprosy outpatient clinic. Subjects and methods: Only the functional status of sexual hormones and male with more of 1 year of Leprosy were evaluated. Clinical data were not evaluated. Measurements were made of their serum levels of free testosterone (FT), luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in 21 patients male with chronic lepromatous disease. The patients were subdivided two groups: up to 60 years (G1) and over 60 years old (G2), due to physiological decline of serum testosterone production in men over 60 years of age. Results: The mean age was 48.43 ± 18.65 years. Serum FT revealed low values in 37.5 % patients. Serum LH, and FSH revealed high values in 18.8 and 6.3% respectively. The mean basal LH and FSH levels were significantly elevated and the level of FT significantly reduced when compared the groups G1 and G2. Furthermore, the G1significantly correlated with low FT levels (P = 0.002). Conclusion: This study showed a high frequency of hypogonadism among male leprosy patients. The assessment of gonadal function to detect hypogonadism should be recommended routinely screening these individuals.<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} -->